Anthracnose of Korean Epimedium Caused by Colletotrichum gloeosporioides - Wan-Gyu Kim; Gyo-Bin Lee; Sung-Kee Hong; Young-Moon Mo; Weon-Dae Cho (한국균학회지)
Anthracnose symptoms were observed on the leaves of Korean epimedium (Epimedium koreanum) plants grown in two fields in Cheolwon, Korea, during disease surveys conducted in September 2019 and 2020. The symptoms were characterized by brown to dark brown, small spots with circular or irregular shapes on the leaves in the early stage. In the later stage, the lesions expanded to 5–10 mm in diameter. The proportion of diseased leaves in the surveyed fields ranged from 10% to 30%. Five single-conidium isolates of Colletotrichum sp. were obtained from the lesions and tested for pathogenicity on Korean epimedium leaves via artificial inoculation. Among the five isolates, only two were pathogenic to the host plant. Anthracnose symptoms induced by these isolates were similar to those observed in the surveyed fields. The Colletotrichum sp. isolates were identified as Colletotrichum gloeosporioides based on their morphological characteristics and phylogenetic analysis. To the best of our knowledge, this is the first report of C. gloeosporioides causing anthracnose in Korean epimedium.